(untitled) (Training and Practice : Journal of Educational Sciences, 2018)
In this work I would like to present my researches made in Pécsi Street Primary School, Kaposvár, where we are improving the pupils’ social competences with the methodology of experiential education. The researches were made in Pécsi Street Primary School, Kaposvár, in years 2-4, twice in every semester with the cooperation of the classes’ form masters. As a result so far it can be said that pupils are more enthusiastic about these activities, making contact with their mates and more efficient in communicating with each other.